Pengaruh Produk, Harga, Tempat Dan Promosi Terhadap Keputusan Konsumen Memilih Jasa Penyewaan Alat Pesta Pada CV. New Abd Production - Rasyid, Abdur; Basalamah, Muhammad Ridwan; Wahono, Budi (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research purpose to determine the Influence of Product, Price, Place and Promotion on Consumer Decisions to Choose Party Equipment Rental Services at CV New ABD Production. This study uses quantitative research methods. The population in this study were Consumers of Party Equipment Rental at CV New ABD Production. While the sample uses Hair's theory with a calculation result of 90 samples. The data used are secondary data and primary data using questionnaire techniques. The data analysis method used is instrument testing: validity testing, reliability testing, Classical assumption testing: normality testing, multicollinearity testing, heteroscedasticity testing, multiple linear regression analysis, hypothesis testing: simultaneous testing, partial testing and coefficient of determination.The results of the study indicate that simultaneously, the four variables of product, price, place, and promotion have a significant effect on consumer decisions. Partially, the results obtained are that the product has a significant effect on consumer decisions. Price has a significant effect on consumer decisions. Place does not have a significant effect on consumer decisions. Promotion has a significant effect on consumer decisions. Keywords: Product, Price, Place, Promotion, Consumer Decisions